Nanotribology and Nanomechanics An Introduction - Bhushan, Bharat (Springer International Publishing : Imprint: Springer, 2017)
This textbook and comprehensive reference source and serves as a timely, practical introduction to the principles of nanotribology and nanomechanics. This 4th edition has been completely revised and updated, concentrating on the key measurement techniques, their applications, and theoretical modeling of interfaces. It provides condensed knowledge of the field from the mechanics and materials science perspectives to graduate students, research workers, and practicing engineers.